Ameliorative effects of ascorbic acid on tolerance to drought stress on pepper (Capsicum annuum L) plants - Khazaei, Zahra (Physiol Mol Biol Plants, 2020)
Drought stress is an important environmental stress that clearly affect biological systems of plants. There is a possibility that growth regulators are able to protect plants under drought conditions. Ascorbic acid (AsA) plays a particular role on growth of plants and protects cells from oxidative damage caused by environmental stresses. This study emphasized the impacts of AsA on improving the drought tolerance of the pepper plants. Based on a factorial arrangement in a completely randomized design, the experiment had two factors. The first factor was drought: irrigation within the field capacity, moderate stress (irrigation within the 60% field capacity) and severe stress (irrigation within the 30% field capacity). The second factor was AsA: 0 mM sprayed with distilled water, 0.5 mM and 1 mM. The experiment had three replications. Drought stress inhibited plant growth parameters including fruit number, height, weight, yield, chlorophyll a and b, total chlorophyll, carotenoid contents, it caused improvement in activity of catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), proline content, anthocyanins, soluble sugars, malondialdehyde (MDA) and H(2)O(2) in the leaves of sweet pepper. Application of AsA contributes to an increase in antioxidant enzymes activity such as SOD, CAT, POD and proline contents, chlorophyll a and b, total chlorophyll, carotenoids, soluble carbohydrates. However, it reduced the content of anthocyanins, MDA and H(2)O(2). Based on this study, it can be suggested that ascorbic acid adjusted antioxidant activity, especially after it has been subjected to drought stress.